Early recovery dynamics of turbid coral reefs after recurring bleaching events. (15th August 2020) - Evans, Richard D.; Wilson, Shaun K.; Fisher, Rebecca; Ryan, Nicole M.; Babcock, Russ; Blakeway, David; Bond, Todd; Dorji, Passang; Dufois, Francois; Fearns, Peter; Lowe, Ryan J.; Stoddart, Jim; et al.
Abstract: The worlds' coral reefs are declining due to the combined effects of natural disturbances and anthropogenic pressures including thermal coral bleaching associated with global climate change. Nearshore corals are receiving increased anthropogenic stress from coastal development and nutrient run-off. Considering forecast increases in global temperatures, greater understanding of drivers of recovery on nearshore coral reefs following widespread bleaching events is required to inform management of local stressors. The west Pilbara coral reefs, with cross-shelf turbidity gradients coupled with a large nearby dredging program and recent history of repeated coral bleaching due to heat stress, represent an opportune location to study recovery from multiple disturbances. Mean coral cover at west Pilbara reefs was monitored from 2009 to 2018 and declined from 45% in 2009 to 5% in 2014 following three heat waves. Recruitment and juvenile abundance of corals were monitored from 2014 to 2018 and were combined with biological and physical data to identify which variables enhanced or hindered early-stage coral recovery of all hard corals and separately for the acroporids, the genera principally responsible for recovery in the short-term (<7 years). From 2014 to 2018, coral cover increased from 5 to 10% but recovery varied widely among sites (0–13%). Hard coral cover typically recovered most at shallower sites that had higher abundance of herbivorous fish, less macroalgae, and lower turbidity. Similarly, acroporid corals recovered most at sites with lower turbidity and macroalgal cover. Juvenile acroporid densities were a good indicator of recovery at least two years after they were recorded. However, recruitment to settlement tiles was not a good predictor of total coral or acroporid recovery. This study shows that coral recovery can be slower in areas of high turbidity and the rate may be reduced by local pressures, such as dredging. Management should focus on improving or maintaining local water quality to increase the likelihood of coral recovery under climate stress. Further, in turbid environments, juvenile coral density predicts early coral recovery better than recruits on tiles and may be a more cost-effective technique for monitoring recovery potential. Highlights: Three thermal anomalies over four years bleached corals and reduced cover by ~90%. Coral recovery varied spatially, limited driven mostly by turbidity. Better water quality increases the likelihood of coral recovery under climate stress. Juvenile coral density predicted early coral recovery better than recruits on tiles.